Media and Conflict Resolution: Toward building a Relationship Model - Noshina Saleem; Mian Ahmad Hanan (Journal of Political Studies, 2014)
The role of media has been immensely increasing in shaping and reshaping the nature of conflicts especially from the second half of the last century. The advent of 24/7 news coverage, advancement in satellite communication, rise of war reporting and peace journalism, and ever increasing role of media in shaping up social, cultural, political and diplomatic discourse has made it an important player in various types of conflicts. Media’s role in conflict resolution is largely dependent upon organizational interests and ideology. This study proposes a Media-Conflict Resolution Model (MCR) that describes the media role in conflict resolution process as (1) an escalation agent, (2) a de-escalation agent and (3) as a mirror, and relates it to media relations with the conflicting parties and consequently the media position/stance either as watchdog, lapdog or neutral. Moreover, this model also discusses influence of global media on local media regarding conflict resolution and prevention.